Ecosystem services under future oil palm expansion scenarios in West Kalimantan, Indonesia - Sharma, S.K.; Baral, H.; Laumonier, Y.; Okarda, B.; Purnomo, H.; Pacheco, P. (Elsevier, 2019)
This study analyzes the five primary ecosystem services and their trade-offs and synergies associated with future scenarios of oil palm plantations in West Kalimantan, Indonesia. Three plausible future scenarios were assessed: 1) business as usual, 2) conservation and, 3) sustainable intensification, based on current land-use policy and spatial planning and projected oil palm expansion. The spatial analysis tool in ArcGIS and the Integrated Valuation of Ecosystem Services and Trade-offs Tool (InVEST Tool) were used to analyze historical and future land-use change, valuation and trade-offs of ecosystem services. The sustainable intensification scenario generates a positive impact on carbon storages and water yield, although habitat quality nominally declines. In terms of total economic value of ecosystem services, the conservation scenario generates the highest value of ecosystem services, while the sustainable intensification scenario offers a compromise solution for future expansion of oil palm by ensuring the supply of ecosystem services comparable to conservation scenario but without significantly affecting palm oil yield in comparison to the business-as-usual scenario. A detailed study with better information on the economic values of ecosystem services can provide a better understanding of the social and environmental impacts of oil palm expansion.